E0204 Heat shock protein 90 enhances rat mesenchymal stem cells migration via PI3KAkt and ERK12 pathways. (17th November 2010) - Feng, Gao; Xinyang, Hu; Xiaojie, Xie; Qiyuan, Xu; Yaping, Wang; Xianbao, Liu; Rongrong, Wu; Meixiang, Xiang; Yong, Sun; Jian-an, Wang
Abstract : Objective: Heat shock protein 90 (HSP90) is a chaperone for several client proteins involved in transcriptional regulation, signal transduction, and cell cycle control. HSP90 is abundantly expressed by a variety of tumour types and has been recently targeted for cancer therapy. The objective of this study is to determine the role of Hsp90 in regulating the migration of Mesenchymal stem cells and to determine the mechanism. We hypothesised that inhibition of Hsp90 impairs the MSCs migration via PI3K/Akt and ERK1/2 signalling pathways. Methods: The MSCs were cultured from femoral and tibia. The ability for MSCs cells to migrate is to be determined by the wound healing assay and transwell assay. The activity of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) were estimated by gelatin –zymography. The mRNA levels of MMP-2, MMP-9, CXCR4 and VCAM-1 were detected by real-time PCR. The protein expression of MMP-2, MMP-9 and ERK1/2, phospho-ERK1/2, Akt and phospho-Akt were determined by Western-blot. Results: Treatment with RhHsp90α significantly enhances MSCs migration from 9.83±2.48 to 48.65±2.81 cells. Treatment with sirhsp90α significantly decreased MSCs migration compared with treatment of hsp90α from 63.33±9.61 to 13.00±4.38 cells. Pretreat with 17-AAG, wortmannin, U0126, decreased MSCs migration to 13.33±1.29, 15.33±2.1, 16.5±3.3 cells, respectively. Treatment with RhHsp90α enhanced the MSCs secretion of MMP-2 and MMP-9, as well as significantly increasing the activity of MMP-9, and increasing the expression of CXCR4 and VCAM-1. PI3K/Akt and ERK signalling pathways mediate the promotion of MSCs migration by RhHsp90α. Conclusions: Our data showed that Hsp90 promotes MSCs migration, elevate the expression of MMP-2, MMP-9, CXCR4 and VCAM-1. PI3K/Akt and ERK signalling pathways mediates these effects. Hsp90 is a candidate drug for enhancement of MSCs migration.